Interaction of rivaroxaban with amiodarone, verapamil and diltiazem in patients with atrial fibrillation: terra incognita - S. N. Bel'diev (Столичная издательская компания, 2016)
Currently there are no generally accepted guidelines for the use of rivaroxaban together with amiodarone, verapamil or diltiazem in patients with creatinine clearance (CrCl)<80 ml/min. Some researchers suggest that in renal failure amiodarone, verapamil and diltiazem contribute to a significant increase in plasma concentrations of rivaroxaban that is accompanied by increased risk of bleeding. According to preliminary calculations, it seems rational to reduce the dose of rivaroxaban when co-administered with these drugs: to 15 mg/day in patients with ClCr 50-79 ml/min and to 10 mg/day in patients with ClCr<50 ml/min.